Graduate school students’ self-efficacy toward online learning in the midst of the COVID-19 pandemic - Rommel Royce Cadapan; Darin Jan Tindowen; Marie Jean Mendezabal; Pyrene Quilang (International Journal of Evaluation and Research in Education (IJERE), 2022)
The COVID-19 pandemic brought drastic changes in graduate education. One of the most pressing concerns that graduate education students experience is their adjustment to the online learning modality. This study was conducted to determine their self-efficacy in online learning. A descriptive method of research was employed by 147 graduate school students in the Northern Philippines. The findings showed that students have a high level of self-efficacy when it comes to online learning. Despite their struggles and challenges in the online classroom, particularly in social interactions and communication with their classmates and teachers, they are eager to complete their respective degrees since they are confident in their learning management system's use. In addition, their current level of self-efficacy in online learning varies according to their age, occupation, and online courses they were previously enrolled in.